Hepatoprotective evaluation of Arogyavardhini Rasa against paracetamol-induced liver damage in rats - Yuga Raj Sapkota; Prashant Bedarkar; Mukesh B Nariya; Pradeep K Prajapati (Wolters Kluwer Medknow Publications, 2017)
Introduction: Liver is termed as Yakrut in ayurvedic classical literature, is one of the major organs for maintaining homeostasis, and is involved more or less with all the biochemical pathways in the body. Arogyavardhini Rasa (AVR) is one of the widely practicing ayurvedic herbo-mineral formulations in liver disorders. It has been used for the management of diverse types of Jvara (fever), Kushtha (skin disorders), Medoroga (altered lipid profiles associated with obesity), and other Yakrit vikara (liver disorders). In this study, AVR was prepared as per the 13th-century classical text Rasaratna Samuchaya. On the other hand, heavy metals causing toxicity, especially mercury present in this formulation, are an issue of concern. Aim of the Study: Hepatoprotective effects of formulation were evaluated by paracetamol (PCM)-induced liver damage in rats to substantiate the role of metal mineral in the classical AVR formulation. Materials and Methods: Effects of formulation were assessed on serum and liver tissue biochemical parameters and histopathological studies. Results: PCM produced significantly impaired the liver and kidney functions as assessed through an increase in liver and kidney marker enzymes. Arogyavardhini-treated group significantly (P = 0.05) prevented this hepatotoxicity and strongly supported by histopathological examinations that revealed AVR shows the protection of liver tissue from PCM-induced hepatotoxicity. Conclusion: The observation of the present study has stalwartly supported the hepatoprotective action of AVR against PCM-induced hepatotoxicity in rats.